Evolution in Time-Use and Division of Labour of Men and Women - Ignace Glorieux; Joeri Minnen; Theun Pieter van Tienoven; Jef Deyaert; Eszter Mészáros (Revue Interventions Économiques)
The way we use our time in general and how we divide paid and unpaid work is affected to a great extend by social and cultural influences. It is also assumed to change in function of social and cultural changes, like more egalitarian attitudes. Many studies, thus, report a decline in paid work and increase in childcare for men and an increase in paid work and labour market participation of women and a decrease in unpaid work. However, the same studies also report a slow convergence in the division of labour between men and women. By using the Flemish 7-day time-use data form 2013 (n=2,894) and by comparing them with the 1999 (n=1,234) and 2004 (n=1,643) comparable time-use data this contribution analyses the evolutions in and current situation of the division of labour between men and women in Flanders, Belgium.  It shows amongst other things that men take up more childcare and women perform more paid work, but that domestic chores remain an equally typical women’s job as in 2004. Additionally, even though the total workload no longer differs significantly between men and women, its composition still does. The convergence to an equal division of labour goes slow, very slow.